Online class, cyberbullying, and internet addiction during COVID-19 and its effect on mental health of UPM undergraduate students - Azlee, Azeelah Yasmin; Abdullah, Haslinda; Zaremohzzabieh, Zeinab (Human Resources Management Academic Research Society (HRMARS), 2023)
The pandemic of COVID-19 is a major public health problem throughout the world. The study conducted is to examine whether the relationship between online classes, Cyberbullying, and internet addiction can affect the mental health of undergraduate students at Universiti Putra Malaysia. The respondent is randomly chosen from students. The study employed quantitative methodology by distributing questionnaires among undergraduate students (n=167). The results of the study show that there is a significant difference in the mental health of depression and stress between male and female students. However, there are contradictory results for the mental health of anxiety the result demonstrated that there was no significant difference in the mental health of anxiety between male and female students. Furthermore, it also was found that there was a significantly correlated in all relationships between online classes and mental health, for Internet addiction and mental health among undergraduate students. There was a contradiction for cyberbullying as the result was only significantly correlated for mental health (stress), mental health (depression) and anxiety was not significantly correlated. The results indicated that both independent variables of cyberbullying and Internet addiction behavior were found to be significant predictors of mental health among undergraduate students. The results of this study are thought to aid other researchers by adding to the scant academic literature in this field.